Valoración de la arboricualtura y lineamientos para el manejo en 12 parques del cantón de Desamparados, San José, Costa Rica - Zúñiga-Sánchez, Brandon (Instituto Tecnológico de Costa Rica, 2017)
The municipality of Desamparados has 231 sites dedicated to the recreation of its inhabitants. The present work shows the results of the evaluation of the arboriculture presented in 12 of these sites. The assessment included the development of the trees, their spatial location, the phytosanitary status, the physical condition, the quality of the maintenance and its impact on the environment. This information is used for the creation of different illustrations that show in what conditions arboriculture is. The trees were classified according to the level of intervention required, this with the aim of generating guidelines that can help the local government in the correct maintenance, management and improvement, of the present and future sites, in favor of the creation spaces with good conditions for visitors and maintaining the balance with the environment and infrastructure in the environment.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Arboricultura urbana; Espacio urbano; Arboricultura; Valoración; Árboles; Municipios